Evaluation of visual design elements of pictures in year four english textbook in selected Malaysian primary schools - Fard, Sara Kasmaienezhad (2018)
Textbooks have been used as the main teaching materials in the schools. This study aims to evaluate the pictures of English textbook in the primary year four through the preferences of students and perceptions of teachers. The study has been conducted in three phases. The first data set consists of two phases of content analysis and descriptive survey. The third phase is related to teachers’ interview. In order to achieve the goals of the study, mixed method triangulation designed is employed. Quantitative method is used for phase one and phase two, the qualitative method is applied in phase three. Data obtained by both methods are interpreted and triangulated simultaneously. All pictures of year-four primary English textbook were analyzed in terms of the colors used in pictures, unusuality, visual content, the connection between picture and text, and visual elements of pictures used in the textbook. Then, the researcher developed a pictorial questionnaire in the form of survey to determine the level of students’ interest to four components of evaluations and different kinds of pictures in terms of their gender. The researcher developed an interview protocol to ask teachers’ opinions on four main components investigated in previous phases. The results of content analysis revealed that there was no coordination among all visual elements (cartoon, graphic, and photograph) as the majority of them were cartoon in the textbook. Finally, it can be noted that unusuality was seen in few pictures of the textbook. Also, the majority of the pictures were simple cartoons in primary and secondary colors which were connected to the text in the textbook. Furthermore, the results showed that the students were highly interested in graphical pictures than cartoons and photos among the visual elements. The results of regression model revealed that students preferred color factor as the most important factor. The unusuality feature had the second order in the preferences of students followed by visual content and visual element factors. The analysis of teachers’ interviews indicated that teachers generally satisfied with the pictures included in the textbook. Teachers were aware of students’ preferences except for visual elements. All teachers believed that cartoons included in the textbook were appropriate for students. The results of this study have some implications for teachers, publishers, illustrators, textbook designers, and textbook developers in the ministry of education.